Molecular biology and medicine at the end of the XXth century - Kornblihtt, A.R. (2000)
This paper reviews basic concepts of modern molecular biology with the premise that its influence in today's medicine is so important that its knowledge cannot remain limited to a few experts. I first analyze the overall structure and organization of human genes, their split nature and the flow of genetic information from DNA to protein. The role of transcriptional control in the regulation of gene expression and cell differentiation is described by introducing experimental examples that define the importance of "master" genes. Basic concepts of genetic engineering, the generation of transgenic and knock out animals and the uses of molecular biology in clinical diagnosis, paternity tests and forensic medicine are presented. Finally, I discuss the possibilities of gene therapy and the fantasies and realities of transgenesis and cloning by nuclear transplant in humans.